Fluorescence lifetime shifts of NAD(P)H during apoptosis measured by time‐resolved flow cytometry. Issue 1 (19th October 2018) - Alturkistany, Faisal; Nichani, Kapil; Houston, Kevin D.; Houston, Jessica P.
Abstract: Autofluorescence from the intracellular metabolite, NAD(P)H, is a biomarker that is widely used and known to reliably screen and report metabolic activity as well as metabolic fluctuations within cells. As a ubiquitous endogenous fluorophore, NAD(P)H has a unique rate of fluorescence decay that is altered when bound to coenzymes. In this work we measure the shift in the fluorescence decay, or average fluorescence lifetime (1–3 ns), of NAD(P)H and correlate this shift to changes in metabolism that cells undergo during apoptosis. Our measurements are made with a flow cytometer designed specifically for fluorescence lifetime acquisition within the ultraviolet to violet spectrum. Our methods involved culture, treatment, and preparation of cells for cytometry and microscopy measurements. The evaluation we performed included observations and quantification of the changes in endogenous emission owing to the induction of apoptosis as well as changes in the decay kinetics of the emission measured by flow cytometry. Shifts in NAD(P)H fluorescence lifetime were observed as early as 15 min post‐treatment with an apoptosis inducing agent. Results also include a phasor analysis to evaluate free to bound ratios of NAD(P)H at different time points. We defined the free to bound ratios as the ratio of 'short‐to‐long' (S/L) fluorescence lifetime, where S/L was found to consistently decrease with an increase in apoptosis. With a quantitative framework such as phasor analysis, the short and long lifetime components of NAD(P)H can be used to map the cycling of free and bound NAD(P)H during the early‐to‐late stages of apoptosis. The combination of lifetime screening and phasor analyses provides the first step in high throughput metabolic profiling of single cells and can be leveraged for screening and sorting for a range of applications in biomedicine. © 2018 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry. Abstract :